A dimensional approach to emotion in infancy: developmental shifts in preferential attention to valence and arousal - Matsuda, Yoshi-Taka; Taniguchi, Kosuke (Frontiers in Developmental Psychology, 2026)
Understanding how infants allocate attention to emotional facial expressions offers crucial insights into the developmental origins of social cognition. This study adopted a dimensional approach focusing on valence and arousal to investigate age-related changes in infants' preferential attention to dynamic facial expressions. Using an eye-tracking paradigm, we examined 234 participants aged 3–36 months, as well as a group of adults, who viewed bilateral presentations of dynamic emotional faces differing in valence (happiness–fear), arousal (anger–disgust), and combined attributes (surprise–sadness). Preferential-looking time at each face and the distribution of gazes toward the eyes or mouth were quantified, and generalized linear models were developed with age, sex, and their interaction as predictors while controlling for individual eye–mouth preferences. In addition, motion-energy differences between paired stimuli were quantified and included as covariates in analyses. Results revealed distinct developmental trajectories across emotional dimensions. Preferences along the valence dimension increased with age; adults attended more to positive (happy) expressions than younger infants. No clear age-related modulation was observed for the arousal dimension under the present stimulus contrast. On the other hand, the combined valence–arousal dimension (surprise–sadness) exhibited a robust inverted-U developmental pattern, peaking between 8 and 12 months. Infants' eye–mouth preferences also followed a U-shaped developmental trajectory, with enhanced mouth focus between 10 and 18 months. Motion-energy analyses demonstrated that perceptual motion salience significantly influenced preferential looking but did not fully account for the observed developmental effects. These findings suggest that sensitivity to valence precedes the differentiation of arousal and that integration of both dimensions undergoes a transient amplification during late infancy. The results support a developmental model in which dimensional sensitivities scaffold later categorical emotion recognition, refining our understanding of early socioemotional specialization.